The Use Of Computer Graphics And Visualisation (From Reconstruction To Training) For The Resource Sector Of Western Australia - Fowle, Kenneth (2003)
The minerals and energy sector can rightly be classified as comprising an extremely hazardous working environment in which numerous situations exist for accidents and incidents involving personnel and equipment to occur.